1961
DOI: 10.1111/j.1550-7408.1961.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Metabolism of L‐Phenylalanine by Tetrahymena performs W*

Abstract: The effect of a series of phenylalanine‐ or tyro‐sine‐containing peptides and derivatives on the oxygen consumption of washed Tetrahymena performers W cells was determined. Peptides gave greater stimulation of oxygen uptake than phenylalanine or tyrosine alone. Intermediary reaction products of phenylalanine metabolism were not oxidized, nor were derivatives of phenylalanine in which the amino group was blocked. The action of several tyrosine or phenylalanine ant metabolites was determined. It was demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It revealed unusual L‐phenylalanine and L‐tyrosine activity (Roth et al. ), and a subsequent publication describing the mechanism for oxidation of these amino acids and their derivatives (Roth and Eichel ). Years later another study enhanced this work using strain WH6 (Perlish and Eichel ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It revealed unusual L‐phenylalanine and L‐tyrosine activity (Roth et al. ), and a subsequent publication describing the mechanism for oxidation of these amino acids and their derivatives (Roth and Eichel ). Years later another study enhanced this work using strain WH6 (Perlish and Eichel ).…”
mentioning
confidence: 99%
“…While pursuing the unique role of L‐lactate in Tetrahymena , he discovered and partially characterized an unusual L‐lactate oxidase, which catalyzes the reaction: L‐lactate + O 2 → pyruvate + H 2 O 2 (Eichel 1960c; Eichel and Rem ,b, ; Roth and Eichel ). Subsequent findings from his laboratory showed that the lactate enzyme may be a general L‐α‐hydroxy acid oxidase, with greater specificity toward α‐hydroxybutyrate than lactate (Eichel 1964b; Eichel et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…REMOLD ?^the^W» that the secretions might act also as pheromones and he «**^%Z^ secondary reservoirs in the males of some Lygaeidae as ^^0^^ when littfe is discharged. Accurate behavioral stud-^ 8U^^^£ some patterns in courtship suggest ^^^^^S^^to proof for pheromonal P-^.^ (CARAYON, the male only (some Anthocondae (CARAYON 19M) P heteropterous 1948), Lethocerus indicus (^^^^^^e^!^ (ROTH, 1961; glands have been suggested, ^/ ung^^ TI M 0NIN , 1961), producing "£?^X^°»* ** °" *"*""* water surface (BRINKHURST, 1960, provided omy w experiments).…”
Section: Scent Apparatusmentioning
confidence: 99%